The Effect of Elevated Basal Follicle Stimulating Hormone Levels on Assisted Reproductive Technology Cycle Outcomes - Inci Kahyaoglu; Hatice Yilmaz Dogru; Sezin Erturk Aksakal; Iskender Kaplanoglu; Serdar Dilbaz; Leyla Mollamahmutoglu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Despite the availability of better biomarkers, basal day 3 follicle-stimulating hormone is widely available and often used as the first-line test in ovarian reserve evaluation. The aim of this study was to evaluate the outcomes of cycles with elevated (>12 IU/mL) basal follicle-stimulating hormone values.